Characteristics of Influenza A/H1N1 complications: ARDS, pneumonia, acute kidney failure, sepsis - review - Lee, Kacper; Skrzypek, Jakub; Niewiadomska, Jagoda; Stępień, Aleksandra; Paluch, Alicja; Bondos , Borys; Niekra, Aleksandra; Fussek, Łukasz; Kochan, Robert; Wieczorek, Ewelina (Journal of Education, Health and Sport, 2025)
Type A h1n1 influenza got its start in 2009 during a pandemic that swept across many countries and contributed to massive mortality. It was characterised by its prevalence among young adults and children. It was associated with fairly common symptoms such as cough, fever and muscle aches, yet it spread rapidly and caused many complications, mainly involving the respiratory system, but also the nervous, circulatory and urinary systems. They often led to long hospital stays and differed in their course and clinical picture from the same diseases of other aetiologies. The aim of this paper is to present the most common complications and demonstrate these differences.